Dietary habits and semen parameters: a systematic narrative review. (20th December 2017) - Ricci, E.; Al‐Beitawi, S.; Cipriani, S.; Alteri, A.; Chiaffarino, F.; Candiani, M.; Gerli, S.; Viganó, P.; Parazzini, F.
Summary: Semen quality and male fertility are declining worldwide. As it was observed that physiologic and pathologic processes of spermatogenesis can be influenced by diet, the relation between dietary habits and semen parameters has been the focus of much interest. To review the human observational studies on this issue, we performed a systematic literature search, up to November 2016 (MEDLINE and EMBASE). We included all observational full‐text papers reporting the relation between dietary habits and semen parameters. Article selection was carried out in accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. Twenty‐three observational studies were included. Overall, 8477 healthy men and 1204 men presenting at Fertility Clinics were included in the selected studies. Even if some inconsistencies are present, possibly due to the different effect of nutrients in fertile and infertile men, results support the hypothesis that diets including fruit and vegetables, for their contents in vitamins, and fish or low‐fat dairy products as the main source of proteins, are associated with better semen quality. Recommendations may be confidently provided because of the many beneficial effects of a healthy diet, although further studies are needed to clarify the currently inconsistent findings and to shed light on the underlying mechanisms.